NEUROMUSCULAR CHORISTOMA - (:unkn) unknown (LIPPINCOTT-RAVEN PUBL, 1995)
Neuromuscular choristomas are rare, with only 13 cases having been previously reported. They usually arise in association with large nerves, and most often occur in the first decade of life. A few have been congenital. Although resection is typically curative, in two instances partial resection alone appears to have been followed by spontaneous regression. The authors report an unusual example of an otherwise classic neuromuscular choristoma where the lesion appeared to grow after incomplete initial resection. Re-excision disclosed a fibromatosis unassociated with choristoma. Despite its wide excision, a recurrence of the fibromatosis required a forequarter amputation. Theories of histogenesis and the clinicopathologic features of the neuromuscular choristomas reported to date are reviewed. The term ''benign Triton tumor,'' although incorrectly applied to this lesion, should be reserved for benign, true nerve sheath neoplasms exhibiting myogenic differentiation.
Keywords: CHORISTOMA; HAMARTOMA; BENIGN TRITON TUMOR; BENIGN TRITON TUMOR; INTRAABDOMINAL FIBROMATOSIS; HAMARTOMA; DIFFERENTIATION